Foetal 25-hydroxyvitamin D moderates the association of prenatal air pollution exposure with foetal glucolipid metabolism disorder and systemic inflammatory responses. (June 2021) - Liu, Yang; Li, Lei; Xie, Jun; Jiao, Xuechun; Hu, Honglin; Zhang, Ying; Tao, Ruixue; Tao, Fangbiao; Zhu, Peng
Highlights: Prenatal air pollution exposure could damage foetal glucolipid metabolic function. Foetal systemic inflammation partly mediates foetal glucolipid metabolism disorder. Foetal 25(OH)D was negatively related to hs-CRP and glucolipid metabolic indexes. High foetal 25(OH)D level may improve foetal hs-CRP level and glucolipid metabolism. Abstract: Background: Previous studies have indicated that systemic inflammation may play an important role in the association between air pollution exposure and glucolipid metabolism disorders, and vitamin D supplementation was beneficial in improving systemic inflammation and glucolipid metabolism. However, the role of foetal 25-hydroxyvitamin D (25(OH)D) and high-sensitivity C-reactive protein (hs-CRP) in the association between prenatal air pollution exposure and foetal glucolipid metabolism disorders is still not clear. Objective: To verify whether foetal 25(OH)D can improve glucolipid metabolism disorders induced by prenatal air pollution exposure by inhibiting the systemic inflammation. Methods: A total of 2, 754 mother-newborn pairs were enrolled from three hospitals in Hefei city, China, between 2015 and 2019. We obtained air pollutants (PM2.5, PM10, SO2, CO, and NO2 ) data from the Hefei City Ecology and Environment Bureau. Cord blood biomarkers (25(OH)D, hs-CRP, C-peptide, HDL-C, LDL-C, TC, and TG) were measured. Results: We found that prenatal air pollution exposure was positively associated with foetal glucolipid metabolic index levels after adjusting for confounders. Additionally, an IQR increase in exposure to PM2.5, PM10, SO2, and CO was associated with 20.0% (95% confidence interval (CI): 16.9, 23.6), 20.1% (16.8, 23.3), 22.9% (20.6, 25.3), and 16.7% (14.4, 19.0) higher cord blood hs-CRP levels, respectively, and an SD increase in hs-CRP was associated with 1.4% (0.1, 2.8), 2.2% (1.6, 2.9), 1.4% (0.9, 2.0), and 3.9% (2.8, 4.9) higher C-peptide, LDL-C, TC, and TG levels in the cord blood, respectively. However, there was a monotonic decrease in β s between cord blood 25(OH)D and biomarkers ( P for trend < 0.001). Furthermore, mediation analysis revealed that the association between air pollution exposure and foetal glucolipid metabolic indexes mediated by hs-CRP and 25(OH)D was 19.35%. In stratified analyses, the significant negative association between cord blood 25(OH)D with foetal hs-CRP and glucolipid metabolic indexes was observed only at low-medium levels of air pollution exposure. Conclusions: Prenatal air pollution exposure could damage foetal glucolipid metabolic function through systemic inflammation. High foetal 25(OH)D levels may improve foetal systemic inflammation and glucolipid metabolism at low-medium levels of prenatal air pollution exposure.